A 3D numerical study on the effects of obstacles on flame propagation in a cylindrical explosion vessel connected to a vented tube. (November 2016) - Luo, C.; Zanganeh, J.; Moghtaderi, B.
Abstract: This article presents a numerical study of the explosive wave propagations from a 40 cm long and 10.8 cm diameter cylinder to smaller 1.7 m and 2.6 m long cylinders with 36 mm diameters. Initially, the 40 cm long cylinder was filled with 4% propane-air mixtures and ignited with a 1 kJ sparking energy until the maximum temperature near the ignition source reached 2400/3000 K. In the study, a 3D numerical model was established by combining compressible four-step reduced propane oxidation reaction kinetics with the k - ω shear-stress transport (SST) turbulent model. In order to resolve the thin detonation wave front, a dynamically refined mesh near the high pressure gradient was adopted. The pressure gradient profiles, velocity magnitude contours, temperature contours and compressible wave propagation speeds across the tubes were then predicted using this 3D model. Highlights: 3D numerical model with reasonable accuracy. The length of the vented tube found to affect the flowing field. A decrease in vented tube diameter increases the flame propagation velocity. Introduction of turbulence by blocks enhances the flame propagation velocity.